2019
DOI: 10.3390/su11226242
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housing Prices on Bank Performance in Korea

Abstract: This study analyzes the relationship between housing prices and bank performance in Korea. To this end, using lending growth, return on assets, and non-performing loans as a performance measure, we estimate fixed-effects models for each measure. Major empirical results are summarized as follows. First, fluctuations in housing prices affect the banks’ lending decisions. If housing prices rise, banks tend to increase the volume of loans. Second, fluctuations in housing prices affect the quality of assets owned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Specifically, it was found that the likelihood of a crisis increases remarkably when bubble-like behaviour in house prices is accompanied by high household leverages (Wan, 2018). However, there are situations where housing prices were found to correlate negatively with NPLs, whereas property prices increase, the same goes to the quality of banking assets, leading to the reduction of NPLs (Ok et al , 2019; Liu et al , 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Specifically, it was found that the likelihood of a crisis increases remarkably when bubble-like behaviour in house prices is accompanied by high household leverages (Wan, 2018). However, there are situations where housing prices were found to correlate negatively with NPLs, whereas property prices increase, the same goes to the quality of banking assets, leading to the reduction of NPLs (Ok et al , 2019; Liu et al , 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Cloyne et al (2017) argue that the impact of housing prices on bank loans in the UK is significant. Ok et al (2019) argue that if housing prices in Korea rise, banks increase their lending and improve their soundness. Unlike these studies, however, some studies show that changes in housing prices have no or negative effects on baning performance.…”
Section: Introductionmentioning
confidence: 99%